GAMBARAN KESESUAIAN PENYIMPANAN OBAT LASA (LOOK ALIKE SOUND ALIKE) DAN OBAT HAM (HIGH ALERT MEDICATION) BERDASARKAN STANDAR PROSEDUR OPERASIONAL DI INSTALASI FARMASI RS.HERMINA GALAXY - Vidia Anwar; Muhammad Fathan N.U; Herty Nur Tanty; Yanthy Susanty (Jurnal Farmasi IKIFA, 2024)
ABSTRACT Patient safety is a system that makes patient care safer, minimizes risk and prevents injury caused by errors resulting from carrying out an action. The goal of patient safety is to increase the safety of high alert medications. High alert medication is a drug that must be watched out for because it often causes errors, sentinel events and drugs that have a high risk of causing Unwanted Drug Reactions (UDR). The purpose of this study was to determine the percentage of suitability for the storage of Look Alike Sound Alike (LASA) and High Alert Medication (HAM) drugs during April 2021 at the Pharmacy Installation of Hermina Galaxy Hospital. The method used in this study was observation on experiment with the results in the form of the percentage of storage and attachment of LASA and high alert drug labels at the Pharmacy Installation of Hermina Galaxy Hospital. This study uses tools such as observation sheets, pens and calculators. The average research results obtained, namely the storage of high alert drugs in April 2021 wass 100% and LASA drugs were 99.8%. The attachment of high alert labels was 98.4% and LASA labels were 98.85%. Based on the results of this study, it can be concluded that the suitability of storing LASA and high alert drugs in the Pharmacy Installation of Hermina Galaxy Hospital is still not in accordance with Standard Operating Procedures.